Church discipline in the Pauline churches: a socio-theological approach - Lee, Sang- Kue (University of the Free State, 2010)
In this study church discipline in the Pauline churches, especially in the churches of the Thessalonians and the Corinthians, was investigated. Traditionally, when New Testament scholars approach church discipline, they tend to concentrate on the nature of the theological issue or on the Question of what kind of theological motive gave rise to the problem. Thus, they research the theological background of the particular offence, what kind of theological issue caused the problem, the background of the church discipline and/or what kind of theological perspective surfaces in the study of church discipline. Some scholars, however, oppose such a "theological approach" and follow another approach, the so called a "sociological approach." They investigate the social and cultural nature of the Biblical text and its environmental backdrop. Disregarding a theological approach, they have contributed studies with a broadened understanding of the sociological character of primitive Christian communities and a focus on the social and cultural conditions that characterized the Biblical world. In this study it is argued that it is not necessary that one approach should exclude the other. The relationship between a "sociological approach" and a "theological approach" should thus not be seen as exclusive and conflicting, but rather as complementary and synthetic. The guiding hypothesis of this study is thus that a combination of a sociological and a theological approach is the best way to explain the problems in the Pauline congregations in Corinth and Thessalonica. In Part II church discipline in the Thessalonian church is examined. The significant problem that occurred in the church of the Thessalonians was that some members of the congregation were idle and caused trouble to the believers and/or non-believers, interrupting other persons' business (2 Thess. 3: l l : cf. 1 Tim. 5: 13). I indicated that this problem embodied both theological and sociological issues: Theologically, there were (1) spiritual enthusiasm, (2) Paul's opponents, and (3) realised eschatology; sociologically there were (1) Hellenistic philosophy such as Epicureanism, (2) voluntary associations, and (3) the system of patronage. In Part III church discipline in the Corinthian church was investigated. The notorious problem that occurred in the church of the Corinthians was that a member of the congregation "has his father's wife" (1 Cor. 5: 1) and that the Corinthian church was proud of it (1 Cor. 5:2). I indicated that this problem of immorality embodied both theological and sociological issues: Theologically, there were (1) Judaisrn, (2) spiritual fanaticism, (3) Christian freedom, and (4) realised eschatology; sociologically, there were (1) Hellenistic philosophy such as Gnosticism, (2) Hellenistic religious cults, and (3) the system of patronage. This study concludes that the two approaches, a "sociological approach" and a "theological approach," should not be taken as exclusive or in conflict, but rather as complementary in order to reach a more suitable answer to the problem of the disorderly in the church of the Thessalonians and that of immorality in the church of the Corinthians.

In hierdie studie word tug in die Pauliniese gemeentes, spesifiek in die gemeentes van Tessalonika en Korinte, ondersoek. Wanneer Nuwe- Testamentici tug ondersoek, neig hulle gewoonlik om te konsentreer op die aard van die teologiese saak of vraagstuk of teologiese motief wat die probleem veroorsaak het. Hulle ondersoek dus die teologiese agtergrond van die spesifieke oortreding, die aard van die teologiese saak wat die probleem veroorsaak het, die agtergrond vir kerklike tug en/of watter tipe teologiese perspektief in die ondersoek van die kerklike tug na vore kom. Ander navorsers opponeer egter so 'n benadering en volg 'n ander benadering, die sogenaamde 'n "sosiologiese benadering." Hulle ondersoek die sosiale en kulturele aard van die Bybelteks en sosiale agtergrond daarvan. Hulle verwerp 'n "teologiese benadering" en lewer studies met 'n breër insig in die sosiologiese aard van die primitiewe Christelike gemeenskappe en 'n fokus op die sosiale en kulturele omstandighede wat die Bybelse wêreld gekenmerk het. In hierdie studie word egter geargumenteer dat dit nie nodig is dat een benadering die ander uitsluit nie. Die verhouding tussen 'n "sosiologiese benadering" en 'n "teologiese benadering" moet dus nie as uitsluitend en botsend van aard ge sien word me, maar eerder as aanvullend en sinteties. Die leidende hipotese van hierdie studie IS gevolglik dat die beste manier om die probleme In die Pauliniese gemeentes Korinte en Tessalonika te verduidelik, , In n kombinasie van die sosiologiese en teologiese benaderings is. In Deel II word tug in die gemeente van Tessalunika ondersoek. Die probleem wat in dié gemeente ontstaan het, is dat sommige gemeentelede nie wou werk nie en probleme vir die gelowiges en/of ongelowiges veroorsaak het en ander mense gepla het (2 Tes. 3: 11; vgl. 1 Tim 5: 13). Ek het aangedui dat hierdie probleem beide teologiese en sosiologiese fasette gehad het. Teologies was daar (1) geestelike oorentoesiasme, (2) Paulus se opponente, en (3) gerealiseerde eskatologie; sosiologies was daar (1) Hellenistiese filosofie, byvoorbeeld Epikurisme, (2) vrywillige verenigings en (3) die patronaatsisteem. In Deel III is tug in die Korintie se gemeente ondersoek. Die berugte probleem in dié gemeente was die feit dat 'n gemeentelid "sy vrou se pa gehad net" (1 Kor. 5: 1) en dat die gemeente daarop trots was (1 Kor. 5:2). Ek het aangedui dat dié probleem beide teologiese en sosiologiese fasette gehad het: Teologies was daar (1) Judaïsme, (2) geestelike fanatisme, (3) Christelike vryheid en (4) gerealiseerde eskatologie; sosiologies was daar (1) Hellenistiese filosofie, byvoorbeeld Gnostiek, (2) Hellenistiese godsdienstige kultusse en (3) die patronaatsisteem. Hierdie studie konkludeer dat die twee benaderings, , n sosiologiese en 'n teologiese benadering, me as uitsluitend of botsend gesien moet word nie, maar eerder as aanvullend en sinteties van aard en dat die probleem van die onordelikes in die gemeente van die Tessalonisense en die probleem van imrnoraliteit in die gemeente van die Korintiërs die beste op dié manier verduidelik kan word.
Thesis (D.Th. (New Testament))--University of the Free State, 2010
Keywords: Church discipline; Theological approach; Sociological approach; Thessalonian congregation; Corinthians congregation; Authorship of 2 Thessalonlans; Idle; Porneia; Patronage; Patronage, Ecclesiastical; Church discipline; Church -- Biblical teaching; Bible. -- N.T. -- Thessalonians -- Criticism, interpretation, etc.; Bible. -- N.T. -- Corinthians -- Criticism, interpretation, etc.